1966
DOI: 10.1017/s0022172400040663
|View full text |Cite
|
Sign up to set email alerts
|

The ecology and epidemiology of the pig-bel syndrome in man in New Guinea

Abstract: 1. Features in the epidemiology of a spontaneous enteric gangrene in the Highlands of New Guinea are described.2. The disease has been called pig-bel because of its firm association with the pig-feasting practices of the people, which occur in 3–7 year cycles.3.Cl. welchiitype C is believed to play an important role in the pathogenesis of the condition. Strains isolated were strongly toxigenic and uniform in their toxin production.4. A food poisoning aetiology was not proved but circumstantial and immunologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Previously we reported the extensive purification of beta toxin produced by C. perfringens type C (9), and suggested that the purified toxin is a thermolabile protein (10) and similar to oxygen-labile toxins produced by other bacteria in being inactivated by oxidizing reagents and activated by reducing reagents (II). Beta toxin produced by C. perfringens type C has been thought to be closely correlated with necrotic enteritis of animals and man (2,4,5,8,14). The diseases are characterized by acute sudden onset, hemorrhagic enteritis, severe hemorrhage into the lumen of the small intestine, and early death.…”
mentioning
confidence: 99%
“…Previously we reported the extensive purification of beta toxin produced by C. perfringens type C (9), and suggested that the purified toxin is a thermolabile protein (10) and similar to oxygen-labile toxins produced by other bacteria in being inactivated by oxidizing reagents and activated by reducing reagents (II). Beta toxin produced by C. perfringens type C has been thought to be closely correlated with necrotic enteritis of animals and man (2,4,5,8,14). The diseases are characterized by acute sudden onset, hemorrhagic enteritis, severe hemorrhage into the lumen of the small intestine, and early death.…”
mentioning
confidence: 99%
“…Strains of C. perfringens used in this study were all type C. Strains CN 5381-5386 and CN 5388, isolated from pig-bel cases in New Guinea (4,5) Assay for beta toxin activity. To estimate beta toxin activity, 0.5 ml of culture filtrate was mixed with a 0.1 ml volume of C. perfringens type A diagnostic serum (Wellcome Laboratories) and 0.2 ml of saline.…”
mentioning
confidence: 99%
“…A possible reason for not using a pit is that, because the land is low-lying and liable to be inundated in the wet season (much of the Bensbach area, for example, is less than 3 m above sea level (Paijmans et al 1971)), the water table is close to the surface for much of the time. Water would lead to disintegration of the clay balls and probably of the termite materials, which is the reason why water is not added to the mumu as is done to generate steam that aids cooking (Sopade 2000) in some other parts of PNG (Murrell et al 1966;Sopade 1997).…”
Section: Anthropology and Medicine 195mentioning
confidence: 99%
“…While the use of conventional river stones in other parts of PNG is no guarantee that all meat in a mumu is thoroughly cooked, as indicated by Murrell et al (1966), only in Morehead District, where pig meat can be infected with Trichinella and poor heatretaining materials are used in mumus, are people placed at risk of acquiring trichinellosis by eating undercooked pig meat prepared in a mumu. (Conditions at Kikori, the other locality in PNG where Trichinella occurs in pigs and also crocodiles, have not been investigated.)…”
Section: Anthropology and Medicine 195mentioning
confidence: 99%